Infection-Associated Thymic Atrophy - Luo, Mingli; Xu, Lingxin; Qian, Zhengyu; Sun, Xi (Frontiers in Immunology, 2021)
The thymus is a vital organ of the immune system that plays an essential role in thymocyte development and maturation. Thymic atrophy occurs with age (physiological thymic atrophy) or as a result of viral, bacterial, parasitic or fungal infection (pathological thymic atrophy). Thymic atrophy directly results in loss of thymocytes and/or destruction of the thymic architecture, and indirectly leads to a decrease in naïve T cells and limited T cell receptor diversity. Thus, it is important to recognize the causes and mechanisms that induce thymic atrophy. In this review, we highlight current progress in infection-associated pathogenic thymic atrophy and discuss its possible mechanisms. In addition, we discuss whether extracellular vesicles/exosomes could be potential carriers of pathogenic substances to the thymus, and potential drugs for the treatment of thymic atrophy. Having acknowledged that most current research is limited to serological aspects, we look forward to the possibility of extending future work regarding the impact of neural modulation on thymic atrophy.